2004
DOI: 10.1002/hbm.20058
|View full text |Cite
|
Sign up to set email alerts
|

Musical training‐induced functional reorganization of the adult brain: Functional magnetic resonance imaging and transcranial magnetic stimulation study on amateur string players

Abstract: We used the combined technique of functional magnetic resonance imaging (fMRI) and transcranial magnetic stimulation (TMS) to observe changes that occur in adult brains after the practice of stringed musical instruments. We carried out fMRI on eight volunteers (aged 20-22 years): five novices and three individuals who had discontinued practice for more than 5 years. The motor paradigm contained a repetitive lift-abduction/fall-adduction movement of the left/right little finger, carried out with maximum efforts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Hypothetically, it may reflect higher intracortical excitability and readiness to provide strong excitatory output despite strong inhibitory input from the surroundings. This capacity may facilitate the mobilization of these motor representational resources during post-lesional changes in the motor network [Fridman et al, 2004;Johansen-Berg et al, 2002;Rossini et al, 2003] or while practising a new motor skill [Karni et al, 1995;Karni et al, 1998;Kim et al, 2004;Kleim et al, 2004;Muellbacher et al, 2001;PascualLeone et al, 1995;Rosenkranz et al, 2007;Tyc et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothetically, it may reflect higher intracortical excitability and readiness to provide strong excitatory output despite strong inhibitory input from the surroundings. This capacity may facilitate the mobilization of these motor representational resources during post-lesional changes in the motor network [Fridman et al, 2004;Johansen-Berg et al, 2002;Rossini et al, 2003] or while practising a new motor skill [Karni et al, 1995;Karni et al, 1998;Kim et al, 2004;Kleim et al, 2004;Muellbacher et al, 2001;PascualLeone et al, 1995;Rosenkranz et al, 2007;Tyc et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in healthy human subjects [Fink et al, 1997;Johansen-Berg et al, 2004;Kim et al, 2004;Partanen et al, 2000;Uozumi et al, 2004] and in patients with brain lesions [Fridman et al, 2004;Ikeda et al, 1992;Krainik et al, 2001;Laplane et al, 1977;Uematsu et al, 1992] have suggested that NPMAs may contain direct corticospinal tracts in addition to the well-known role in the selection and motor control of complex movements via cortico-cortical networks. In non-human primates, it has been well established that, the NPMAs in the frontal lobe contain multiple fore-and hindlimb muscles representation areas with monosynaptic connections to lower motor neurones [Boudrias et al, 2010a;Boudrias et al, 2010b;Dum and Strick, 1991;Dum and Strick, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…After left hemisphere lesions impair basic motor function, homologous right hemisphere structures begin to compensate over time [82]. Learning (or relearning) the playing of a stringed instrument leads to an experience-based reorganization of the left parietal and premotor cortices [83]. Activity related to spatial processing in a patient with a parietal lesion shifts from the left to right parietal lobe, suggesting plasticity of higher level processes as well [84].…”
Section: Rehabilitation Of Ima Patientsmentioning
confidence: 98%
“…This implies an important potential of art for an individual's development of affective sensitivity to interpersonal communication. Something similar seems to occur with musical practice and painting expertise …”
Section: Six Functions Of Dance?mentioning
confidence: 81%